A flow visualization study of an anatomic coronary artery anastomosis model with an implant - Pedroso, Pedro D.; Advincula, Maria A.; Anayiotos, Andreas (My University, 2003)
Flow Streamlining Devices is a new tool in Coronary Artery Bypass Grafting (CABG). They aim in: a) Performing a sutureless anastomosis to reduce thrombosis at the veno-arterial junction, and b) Providing a hemodynamically efficient scaffolding to reduce secondary flow disturbances. Thrombosis and flow disturbances are factors that have been reported as contributing factors to the development of intimal hyperplasia (IH) and failure of the graft. By reducing thrombosis and flow disturbances, it is expected that IH will be inhibited and the lifetime of the graft extended. To evaluate the hemodynamic benefits of such an implant, two models were designed and fabricated. One simulated the geometry of the conventional anastomosis without an implant, and the other simulated an anastomosis with a flow streamlining implant. Identical flow conditions relevant to a coronary anastomosis were imposed on both models and flow visualization was performed with dye injection and a digital camera. Results showed reduction of disturbances in the presence of the implant. This reduction seems to be favorable to hemodynamic streamlining which may create conditions that may inhibit the initialization of IH. However, the compliance and geometric mismatch between the anastomosis and the implant created a disturbance at the rigid compliant wall interface, which should be eliminated prior to clinical applications.
Keywords: Flow visualization; Hemodynamics; Coronary arteries--Stenosis